The Linguistic Modernity among Youth Culture: The Moroccan Linguistic Context - Assiya AIT MAMA (Journal of English Language Teaching and Linguistics, 2023)
This paper seeks to examine linguistic modernity within Moroccan youth culture in the context of social interactions. The study specifically focuses on the lexical and topical aspects of linguistic practices among young individuals. The research employs a combination of questionnaires and unstructured interviews to gather relevant data, which will then be subjected to a mixed-method analysis. The qualitative aspect involves analysing recorded interviews using discourse analysis, focusing on participants' interactions and examining the linguistic components of youth language, including lexicon and distinctive topics that differentiate them from older social groups. On the quantitative side, the research measured participants' utilization of innovations, code-switching, and compared gender-related aspects of youth language. This paper delved into various aspects of linguistic modernity within youth culture, particularly focusing on lexical and topical dimensions. Concerning lexicon, the results of the study revealed that young individuals forge novel collocations by creatively employing language. They incorporate slangs, both general and internet-specific, into their speech. Moreover, these youths display a propensity for inter-sentential code-switching, utilizing multiple languages in their discourse. Notably, social media and technology emerge as predominant themes in their conversations. While youth language is a distinctive facet of their linguistic behaviours, paralinguistic practices also exemplify their generational characteristics. Likewise, the quantitative findings collectively suggest that young people in Morocco are adaptable in their language usage, often incorporating new expressions from various sources, code-switching, and displaying an interest in both Western and Asian languages.